Preparation of bioinspired graphene oxide/PMMA nanocomposite with improved mechanical properties. (10th November 2021) - Chathuranga, Hiran; Chandula Wasalathilake, Kimal; Marriam, Ifra; MacLeod, Jennifer; Zhang, Zhanying; Bai, Ruixiang; Lei, Zhenkun; Li, Yan; Liu, Yinong; Yang, Hong; Yan, Cheng
Abstract: Strength and toughness have been often considered as mutually exclusive properties in many synthetic materials. Natural materials like nacre have overcome this conflict by optimizing internal architecture at the nanoscale. In this work, nacre-inspired graphene oxide (GO)-poly (methyl methacrylate) (PMMA) nanocomposite is fabricated, which has a "brick and mortar" microstructure and enhanced interfacial strength. It has a tensile strength of 261 ± 7 MPa and toughness of 5 ± 0.2 MJ m −3, which are 55% and 42% greater than conventional GO/PMMA nanocomposites. In addition, the nanocomposite has excellent stability in wet environments. This work, therefore, provides a facile method to fabricate novel nanocomposites with improved mechanical properties. Graphical abstract: Image 1